2019
DOI: 10.1051/parasite/2019074
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of host immune cells and cytokine production induced byTrichinella spiralisinfection

Abstract: The nematode Trichinella spiralis can cause immunoregulation during the early phase of infection. However, previous studies are still insufficient for a full understanding of this phenomenon and its underlying mechanism. In this study, immune cells and cytokine profiles of T. spiralis infected mice were examined by Meso Scale Discovery (MSD) and flow cytometry. The MSD results of the spleen showed that Th1 immunity was inhibited from 6 h to 6 days post-infection (dpi) and the level of Th2 immune response was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…Our findings are similar to the results reported in the study by Song et al, in which it was observed, in an experimental mouse model, a Th2 immune response was presented, with a significant increase in Th2 cytokines (IL-4/IL-10) after the third day of T spiralis infection. 42 Resistance to most gastrointestinal helminths is mediated by Th2 cytokine immune responses. 43 In T spiralis infection, IL-13, IL-4Rα and IL-4 play an important role, since they are necessary for way, observing the IL-4Rα expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are similar to the results reported in the study by Song et al, in which it was observed, in an experimental mouse model, a Th2 immune response was presented, with a significant increase in Th2 cytokines (IL-4/IL-10) after the third day of T spiralis infection. 42 Resistance to most gastrointestinal helminths is mediated by Th2 cytokine immune responses. 43 In T spiralis infection, IL-13, IL-4Rα and IL-4 play an important role, since they are necessary for way, observing the IL-4Rα expression.…”
Section: Discussionmentioning
confidence: 99%
“…In order to elucidate more about the protective effect of RTX treatment in the intestinal phase of T spiralis infection, in this study, the RTX effect on the number of mast cells in intestinal tissue was evaluated, as well as intestinal expulsion of T spiralis, since it is known that mast cells, as part of the Th2 immune response, are involved in the T spiralis expulsion. 17,65,66 Several studies have shown that during the intestinal phase of T spiralis infection, there is an increase in the number of mast cells 32 in intestinal tissue, 42 while at the same time there is a reduction in number of adult worms of T spiralis, 33,34,49,67 indicating that intestinal mastocytosis favours the intestinal expulsion of T spiralis. 16,59 In Figure 7, it is observed that on day 0 p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that T. spiralis could elicit a predominant Th1 response at the initial intestinal phase and subsequently converts into Th2 type response [ 11 ]. The well-characterized type 2 cytokine response is beginning at the adults orchestrating niches in intestinal epithelial cells and persists during the whole chronic infection [ 16 18 ]. The Th2 immune response is characterized by the production of high levels of IL-4, IL-5, IL-9, and IL-10 [ 19 ], where IL-4 has been suggested to provide support for nematode growth through the production of IgE and tissue injury [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a zoonotic nematode and foodborne parasite, T. spiralis infection leads to the suppression of the host immune response [13]. According to a previous study, T. spiralis antigens induce a mixed Th1/Th2 cytokine profile with a predominance of Th2 cytokines (IL-4, IL-6, and IL-10) increases [6,35]. In this study, ML, ADs, and NBL ESPs were used as T. spiralis antigens.…”
Section: Discussionmentioning
confidence: 99%